PENGARUH STRUKTUR MODAL DAN PERTUMBUHAN PENJUALAN TERHADAP PROFITABILITAS PADA PERUSAHAAN SUB SEKTOR OTOMOTIF DAN KOMPONEYANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2016-2019 - Restia Christianty; Meiske Wenno; Patresia Natalia Erlely (Soso-Q : Jurnal Manajemen, 2021)
AbstractThis study to aims determine the effect of capital structure and sales growth on profitability in the sub-sector of automotive and component companies listed on the Indonesian stock exchange for the 2016-2019 period. The dependent variable in this study is profitability, while the independent variables are capital structure and sales growth. This study also uses firm size as a control variable. The sampling methodused purposive sampling method with a sample of 6 automotive and component sub-sector companies listed on the Indonesian stock exchange for the 2016-2019 period. The data analysis technique used is multiple linear regression analysis. The results showed that capital structure (DER) had a negative and insignificanteffect on profitability (ROA) and sales growth (SALES) had a positive and significant effect on profitability (ROA). Firm size (SIZE) as a control variable has a positive and significant effect on profitability (ROA).Keywords: Capital Structure, Sales Growth, and Profitability